Challenges and Opportunities: Transition to Online Streaming Performances in the South African Opera Industry (Proceeding of the International Conference on Arts and Humanities, 2022)
The COVID-19 pandemic has caused a profound sense of uncertainty and insecurity in the world of opera. The COVID-19 pandemic has emerged as a phenomenon that is brutally affecting the opera industry. This effect was most prevalent and predominant in developing countries. Within a short period, the COVID-19 pandemic triggered unprecedented turmoil in the world of the arts. In European countries, many well-established opera companies opted for online streaming. The seismic disruption brought by the protocols imposed by the COVID-19 pandemic confirms the importance of changing from the traditional method of performance. Hence, this paper explores the challenges and opportunities of the transition to online streaming performances in the South African opera industry. A qualitative research method was employed using reviews of scholarly writings and informal interviews with opera singers and managers of opera companies. A thematic analysis was adopted to analyse the findings. The findings were presented in themes, namely 1. Challenges and opportunities of the transition to online streaming performance; 2. Effect of the national lockdown in South African opera industry; 3. Vulnerability of opera singers in the South African opera industry. The findings demonstrate that the South African opera industry was hit hard by the pandemic. The severity of the impact is partly attributable to the lockdown the South African government imposed to curb the spread of coronavirus. This paper concludes by stating that online streaming performances could be a longstanding solution for the opera industry.
Keywords: COVID-19 pandemic; challenges; opera industry; opportunities; online streaming; lockdown; vulnerability